Hadith #293 - Sahih al-Bukhari - al-Qasim Abu 'Abdur Rahman Ø§ÙÙØ§Ø³Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ ÙÙÙØ§Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙ (Sahih al-Bukhari)
`Aisha said, âWe set out with the sole intention of performing Hajj and when we reached Sarif, (a place six miles from Mecca) I got my menses. Allahâs Messenger (ï·º) came to me while I was weeping. He said âWhat is the matter with you? Have you got your menses?â I replied, âYes.â He said, âThis is a thing which Allah has ordained for the daughters of Adam. So do what all the pilgrims do with the exception of the Tawaf (Circumambulation) round the Ka`ba.â `Aisha added, âAllahâ
Grade: Sahih

Hadith #2383 - Sahih al-Bukhari - al-Qasim Abu 'Abdur Rahman Ø§ÙÙØ§Ø³Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ ÙÙÙØ§Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙ (Sahih al-Bukhari)
Aisha said that she hung a curtain decorated with pictures (of animals) on a cupboard. The Prophet (ï·º) tore that curtain and she turned it into two cushions which remained in the house for the Prophet (ï·º) to sit on.
Grade: Sahih

Hadith #4548 - Sahih al-Bukhari - al-Qasim Abu 'Abdur Rahman Ø§ÙÙØ§Ø³Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ ÙÙÙØ§Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙ (Sahih al-Bukhari)
Ibn `Abbas asked `Aishaâs permission to enter. Al-Qasim then narrated the whole Hadith (as in 277) but did not mention: âWould that I had been forgotten and out of sight.â
Grade: Sahih

Hadith #5112 - Sahih al-Bukhari - al-Qasim Abu 'Abdur Rahman Ø§ÙÙØ§Ø³Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ ÙÙÙØ§Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙ (Sahih al-Bukhari)
Aisha said, âWhat is wrong with Fatima? Why doesnât she fear Allah?â by saying that a divorced lady is not entitled to be provided with residence and sustenance (by her husband).
Grade: Sahih

Hadith #5113 - Sahih al-Bukhari - al-Qasim Abu 'Abdur Rahman Ø§ÙÙØ§Ø³Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ ÙÙÙØ§Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙ (Sahih al-Bukhari)
Urwa said to Aisha, âDo you know so-and-so, the daughter of Al-Hakam? Her husband divorced her irrevocably and she left (her husbandâs house).â `Aisha said, âWhat a bad thing she has done!â âUrwa said (to `Aisha), âHavenât you heard the statement of Fatima?â `Aisha replied, âIt is not in her favor to mention.â âUrwa added, `Aisha reproached (Fatima) severely and said, âFatima was in a lonely place, and she was prone to danger, so the Prophet (ï·º) allowed her (to go out
Grade: Sahih

Hadith #6711 - Sahih al-Bukhari - al-Qasim Abu 'Abdur Rahman Ø§ÙÙØ§Ø³Ù Ø£Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙÙ ÙÙÙØ§Ù Ø¨Ù Ø¹Ø¨Ø¯ Ø§ÙØ±ØÙ (Sahih al-Bukhari)
A woman from the offspring of Ja`far was afraid lest her guardian marry her (to somebody) against her will. So she sent for two elderly men from the Ansar, `AbdurRahman and Mujammiâ, the two sons of Jariya, and they said to her, âDonât be afraid, for Khansaâ bint Khidam was given by her father in marriage against her will, then the Prophet (ï·º) cancelled that marriage.â (See Hadith No. 78)
Grade: Sahih